Kerusakan Lima Varietas Padi Akibat Serangan Hama Penggerek Batang di Desa Savanajaya, Kecamatan Waeapo, Kabupaten Buru - Muhamad F Umakamea; John A Patty; Ria Y Rumthe (JURNAL BUDIDAYA PERTANIAN, 2020)
One of the obstacles in efforts to increase rice productivity is the damage caused by the attack of the rice stem borer. Annual yield loss caused this insect pests is quite high, reaching 10-30%. The attack of stem borer has long been encountered and is a problem in rice producing areas on Buru Island, such as in Savanajaya Village. This study aimed to obtain data on the types of pests, population levels and the intensity of damage in five rice varieties due to stem borer attact and to determine the varieties that had the lowest population and damage intensity in the Saavanajaya Village, Waeapo District, Buru Regency. The method used was a survey method that focused on five varieties of rice cultivated by farmers, to obtain population data and the intensity of damage. The results showed that the type of pest that attacked the five rice varieties of IR-64 variety in Savanajaya Village was the white rice stem borer (Scirpophaga innotata), with the highest larval population (per cluster) of 1.27 individuals and the intensity of damage 5.20%, followed by Cigeulis variety with a larval population of 1.17 individuals and damage intensity of 4.70%, the Ciherang variety with a larval population of 1.07 individuals and damage intensity of was 4.25%, the Mekongan variety with a larval population of 1.1 individuals and damage intensity of 4.15%, and the lowest was the Membramo variety with a larval population of 1.03 larvae and damage intensity of 4.12%. The damage intensity of at the study site, although different between varieties, could all be classified into the category of mild attack. Keywords: damage intensity, rice varieties, Savanajaya, stem borer ABSTRAK Salah satu kendala dalam upaya peningkatan produktivitas padi adalah kerusakan yang disebabkan oleh serangan penggerek batang padi. Kehilangan hasil setiap tahun yang disebabkan oleh serangga hama ini padi cukup tinggi, bisa mencapai 10-30%. Serangan hama penggerek batang telah lama ditemui dan menjadi masalah di daerah produsen padi di Pulau Buru, seperti di Desa Savanajaya. Penelitian ini bertujuan untuk mendapatkan data jenis hama, jumlah populasi serta intensitas kerusakan pada lima varietas padi akibat serangan hama penggerek batang serta menentukan varietas yang memiliki populasi dan intensitas kerusakan terendah di Desa Savanajaya, Kecamatan Waeapo, Kabupaten Buru. Metode yang digunakan adalah survey yang difokuskan pada lima varietas padi yang diusahakan petani, untuk mendapatkan data populasi dan ntensitas kerusakan. Hasil penelitian menunjukkan bahwa jenis hama yang menyerang lima varietas padi varietas IR-64 di Desa Savanajaya adalah penggerek batang padi putih (Scirpophaga innotata), dengan populasi larva (per rumpun) tertinggi 1,27 ekor dan intensitas kerusakan 5.20%, diikuti oleh varietas Cigeulis dengan populasi larva 1,17 ekor dan internsitas kerusakan 4.70%, varietas Ciherang dengan populasi larva 1.07 ekor dan intensitas kerusakan 4.25%, varietas Mekongan dengan populasi larva 1.1 ekor dan intensitas kerusakan 4.15 %, dan yang terendah varietas Membramo dengan populasi larva 1.03 ekor dan intensitas kerusakan 4.12%. Intensitas kerusakan di lokasi penelitian, walaupun berbeda antar varietas tetapi semuanya dapat diklasifilasikan ke dalam kategori serangan ringan. Kata kunci: intensitas kerusakan, penggerek batang, Savanajaya, varietas padi,